The Existence of Traditional Market in the Middle of Modern/HighClass Settlement - Siregar, Adisya Puteri; Sri Suryani Yuprapti Winasih (Jurnal Koridor, 2024)
In big cities, the construction of residential neighborhoods is mostly done to meet the needs for housing. But often this development isn’t matched by the need for public and social facilities. Markets are included in public and social facilities that are rarely built in the environment, especially traditional markets. The existence of traditional markets is rarely found as a result of the development of modernization. However, several settlements still provide traditional markets as a facility in a settlement, one of which is in a modern settlement. This study aims to find out some modern or highclass settlements that still maintain traditional markets as public and social facilities. The research was conducted in two markets with different environments but still in the same circle, it’s Citraland Fresh Market in Surabaya and Batunanggal Market in Bandung. Both are traditional markets packed in modern buildings. Data collection techniques using qualitative methods in the form of observation, documentation, and existing journals. Conclusions are written based on direct observation by the author and the results of the data analysis that has been collected.